2011
DOI: 10.1007/s00436-011-2366-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Legionella and their host amoebae from weak alkaline carbonate spring water using a culture method combined with PCR

Abstract: Legionella were detected with the direct DNA extraction method, Legionella culture method, and free-living amoebae (FLA) culture method from weak alkaline carbonate spring water in Taiwan. Moreover, we also investigated the existence of Acanthamoeba, Hartmannella, and Naegleria, ubiquitous FLA in aquatic environments, to identify the correlations between existing Legionella. This study reports detecting Legionella in 15 of the 51 weak alkaline carbonate spring water samples (29.4%). This work also found five o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…was detected in the raw and finished water of all DWTPs and WWTPs, indicating that the purification processes used in these treatment plants did not eliminate this opportunistic agent. This fact is important to highlight since such amoebae have been described as vectors or reservoirs of pathogenic microorganisms (Scheid et al 2008;Valster et al 2011;Huang et al 2011). Our results are not surprising, since similar data have been obtained by the previous reports from DWTP.…”
Section: Discussionsupporting
confidence: 79%
“…was detected in the raw and finished water of all DWTPs and WWTPs, indicating that the purification processes used in these treatment plants did not eliminate this opportunistic agent. This fact is important to highlight since such amoebae have been described as vectors or reservoirs of pathogenic microorganisms (Scheid et al 2008;Valster et al 2011;Huang et al 2011). Our results are not surprising, since similar data have been obtained by the previous reports from DWTP.…”
Section: Discussionsupporting
confidence: 79%
“…and Naegleria spp., all commonly found in fresh water. Some have suggested that culturing for free-living amoebae from a suspected water source may increase the sensitivity of Legionella detection [27]. …”
Section: Legionellamentioning
confidence: 99%
“…According to the authors, no significant correlation was found between the number of Legionella and the temperature of the samples (≥40°C). Legionella , capable of reproducing at temperatures between 25 and 50°C and surviving at temperatures of up to 55–60°C, thrive in both natural and anthropogenic hot water systems .…”
Section: Discussionmentioning
confidence: 99%
“…They have been identified in both natural and anthropogenic water bodies (rivers, ponds, lakes, thermal springs as well as swimming pools, cooling towers, water distribution networks) . They are also found in brine baths filled with thermal saline deepwater .…”
Section: Introductionmentioning
confidence: 99%